Iron and Magnesium Impregnation of Avocado Seed Biochar for Aqueous Phosphate Removal - Jihoon Kang; Jason Parsons; Sampath Gunukula; Dat T. Tran (Clean Technologies, 2022)
There has been increasing interest in using biochar for nutrient removal from water, and its application for anionic nutrient removal such as in phosphate (PO43−) necessitates surface modifications of raw biochar. This study produced avocado seed biochar (AB), impregnated Fe- or Mg-(hydr)oxide onto biochar (post-pyrolysis), and tested their performance for aqueous phosphate removal. The Fe- or Mg-loaded biochar was prepared in either high (1:8 of biochar to metal salt in terms of mass ratio) or low (1:2) loading rates via the co-precipitation method. A total of 5 biochar materials (unmodified AB, AB + High Fe, AB + Low Fe, AB + High Mg, and AB + Low Mg) were characterized according to their selected physicochemical properties, and their phosphate adsorption performance was tested through pH effect and adsorption isotherm experiments. Fe-loaded AB contained Fe3O4, while Mg-loaded AB contained Mg(OH)2. The metal (hydr)oxide inclusion was higher in Fe-loaded AB. Mg-loaded AB showed a unique free O–H functional group, while Fe-loaded AB showed an increase in its specific surface area more than 10-times compared to unmodified AB (1.8 m2 g−1). The effect of the initial pH on phosphate adsorption was not consistent between Fe-(anion adsorption envelope) vs. Mg-loaded AB. The phosphate adsorption capacity was higher with Fe-loaded AB in low concentration ranges (≤50 mg L−1), while Mg-loaded AB outperformed Fe-loaded AB in high concentration ranges (75–500 mg L−1). The phosphate adsorption isotherm by Fe-loaded AB fit well with the Langmuir model (R2 = 0.91–0.96), indicating the adsorptive surfaces were relatively homogeneous. Mg-loaded biochar, however, fit much better with Freundlich model (R2 = 0.94–0.96), indicating the presence of heterogenous adsorptive surfaces. No substantial benefit of high loading rates in metal impregnation was found for phosphate adsorption. The enhanced phosphate removal by Mg-loaded biochar in high concentration ranges highlights the important role of the chemical precipitation of phosphate associated with dissolved Mg2+.